MEMAHAMI DOKTRIN SYIAH DALAM BINGKAI TOLERANSI - Ahmad Ali MD (Harmoni, 2015)
Understanding Shia doctrine cannot be separated from its point of view. Its mainstream view is certainly not always right. Non-mainstream view is more relevant and more proper in portraying Shia and its doctrine. The sixth Muslim pillars and Islamic jurisprudence are different from mainstream doctrines (Sunni doctrines) but they are not considered as deviance because they have their own various perspectives. It can be seen from mut’ah marriage that is not absolute; there is a relevant perspective revealed by Ja‘far al-Subhânî. He states that mut’ah marriage is allowed by some determined requirements and unlike common view discrediting its perspective. Therefore to understand Shia doctrine at least is needed five non-authoritative interpretations such as honesty, perseverance, comprehensiveness, rationality, and selfcontrol. Those understandings contribute to tolerance towards Shia.